Structures of a non-ribosomal peptide synthetase condensation domain suggest the basis of substrate selectivity - Thierry Izoré (Nature Portfolio, 2021)
Non-ribosomal peptide synthetases (NRPSs) are multi-modular enzymes assembling complex natural products. Here, the structures of a Thermobifida fusca NRPS condensation domain bound to the substrate-bearing peptidyl carrier protein (PCP) domain provide insight into the mechanisms of substrate selectivity and engagement within the catalytic pocket.